Transvenous pacing leads implanted in epicardial position: A recipe for future epicardial pacing electrode?Central MessagePerspective - Seraina Brütsch, MD; Christian Balmer, MD; Hitendu Dave, MD (JTCVS Techniques)
Objective: Finding an optimum epicardial pacing site in children needing lead replacement can be challenging. We report the midterm outcome of using transvenous SelectSecure leads in the epicardial position. Methods: Between 2018 and 2020, 6 patients (5 children and 1 adult) received 8 SelectSecure 3830 leads (“off-label”) in the epicardial position: both the left atrium and left ventricle in 2 patients, only the left ventricle in 3 patients, and the right ventricle in 1 patient. The median age at lead implantation was 14 (4-35) years. Periodic pacing threshold, sensing, and impedance measurements were analyzed. Results: Lead implantations could be performed in all patients without complications, despite scarring from previous surgeries. The median pacing, sensing, and impedance measurements for 6 ventricular leads were 0.75 V, 6.5 mV, and 576 Ohm, respectively. The same for 2 atrial leads were 1.25 V, 2.5 mV, and 758 Ohm, respectively. During a follow-up period of 23.4 (8-32) months, despite a small increase at 6 months, pacing and sensing parameters remained acceptable. One reoperation occurred after the follow-up period due to lead dysfunction. One young patient with a complex structural heart disease and terminal heart failure on a ventricular assist device died while waiting for a heart transplant. Conclusions: The implantation of transvenous leads in the epicardial position is feasible and provides an alternative for cardiac pacing in patients with multiple previous surgeries and epicardial scarring. This lead design, although appealing, poses challenges for stable epicardial fixation. A larger experience and longer follow-up would decide its exact role in epicardial pacing.